Lightweight long-life flooded battery and preparation method thereof

By using PE glass fiber layer wrapping and PE glass fiber partition design in lead-acid batteries, combined with high-visual density lead paste and appropriate curing and drying technology, the problem of weight reduction and life improvement of lead-acid batteries under the operating conditions of new energy vehicles is solved, and the effect of weight reduction and life extension is achieved.

CN119650886APending Publication Date: 2025-03-18ANHUI LEOCH POWER SUPPLY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411925832.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The operating conditions of new energy vehicles require lead-acid batteries to reduce their weight and improve their service life while the volume remains unchanged.

Method used

A lightweight, long-life liquid-rich battery is designed. By using PE glass fiber layer wrapping and PE glass fiber partitions in the positive and negative electrode plates, combining high-visual density lead paste and appropriate curing and drying process, the binding force between the electrode plate and the lead paste is improved, and the shedding of active substances is reduced through interference design.

Benefits of technology

It is achieved by reducing the weight by about 8% while the battery capacity remains unchanged, and significantly improving the service life of the battery, which is more than 50% higher than the comparative example.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a light-weight long-life flooded battery and a preparation method thereof, and relates to the technical field of lead-acid storage batteries. The light-weight long-life flooded battery comprises a positive electrode group, a negative electrode group, a partition plate and a battery shell, the positive electrode group is composed of positive plates wrapped by PE glass fiber layers, the negative electrode group is composed of negative plates, and the positive electrode group and the negative electrode group are in interference fit with the battery shell; the partition plate is a PE glass fiber partition plate. The battery preparation method comprises the following steps: preparing the positive plate, the negative plate and the separator; wrapping the positive plate with a PE glass fiber layer, and then preparing a positive electrode group and a negative electrode group; and assembling the positive electrode group, the negative electrode group and the partition plate into the battery shell, wherein the positive electrode group and the negative electrode group are in interference fit with the battery shell. According to the invention, the PE glass fiber separator is adopted, compared with a conventional separator, a PE layer is added, the thickness of the pole group is increased, and the positive pole group and the negative pole group are in interference assembly in the battery shell in cooperation with the structural design of the invention, so that the falling of active substances in the use process of the storage battery is reduced, and the service life is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lead-acid batteries, and in particular to a lightweight, long-life, liquid-flooded battery and a preparation method thereof. Background Art

[0002] In recent years, in response to the national call, more and more car companies have invested in the development of new energy vehicles. The use environment and working conditions of lead-acid batteries in new energy vehicles and traditional fuel vehicles have changed. Compared with traditional fuel vehicles, the use environment temperature of starting lead-acid batteries in new energy vehicles is not high, and there is no need to start the fuel engine, and high CCA is not required. In order to ensure the endurance of new energy vehicles, each component needs to be lightweight, and the design of lead-acid batteries needs to be changed to adapt to the use conditions of new energy vehicles. The battery shell size is required to remain unchanged, the weight is reduced, and the life is increased. Summary of the invention

[0003] In order to solve at least one of the above technical problems, a battery with reduced weight and increased service life while maintaining unchanged volume is developed. The present application provides a lightweight, long-life, liquid-filled battery and a preparation method thereof.

[0004] On the one hand, the present application provides a lightweight, long-life liquid-flooded battery, comprising a positive electrode group, a negative electrode group, a separator and a battery shell; the positive electrode group is composed of a plurality of positive electrode plates, and each positive electrode plate is wrapped by a PE glass fiber layer, the negative electrode group is composed of a plurality of negative electrode plates, and the positive electrode group, the negative electrode group and the battery shell are interference fit; the separator is a PE glass fiber separator.

[0005] Optionally, the positive electrode plate includes a positive electrode grid and a positive electrode lead paste;

[0006] The positive electrode lead paste is prepared from the following components in parts by weight:

[0007] 2.5-3 parts of sodium perborate;

[0008] 1-2 parts of graphite;

[0009] Glass fiber 0.8-1 part;

[0010] Lead powder 950-1050 parts;

[0011] 90-110 parts of deionized water;

[0012] 90-100 parts of dilute sulfuric acid;

[0013] Optionally, the preparation method of the positive electrode lead paste is as follows:

[0014] Weigh the formulated amount of sodium perborate, graphite, and glass fiber into a pot, add the formulated amount of lead powder, and dry-mix for 5 to 10 minutes to obtain a mixture;

[0015] Add the formulated amount of deionized water to the mixture and continue stirring for 3 to 5 minutes;

[0016] Add the formulated amount of dilute sulfuric acid, and control the addition of sulfuric acid within 13 to 15 minutes. After the addition of dilute sulfuric acid is completed, continue stirring for 5 to 10 minutes.

[0017] Optionally, the preparation method of the positive electrode plate is as follows:

[0018] The positive lead paste is applied on the positive grid, 100-110g of the positive lead paste is applied on each positive grid, and the positive lead paste covers the positive grid by 0.2-0.3mm to obtain a positive plate. After the positive plate is surface dried at 170-220°C, the positive plate is cured and dried.

[0019] Optionally, the curing and drying adopts a temperature and high humidity curing process; the curing time is 24 to 48 hours, the curing temperature is 50°C, the relative humidity is 80 to 99%, the drying time is 20 to 24 hours, and the drying temperature is 60 to 80°C.

[0020] The above technical solution can improve the bonding strength between the positive electrode plate and the positive electrode lead paste.

[0021] Optionally, the negative electrode plate includes a negative electrode grid and a negative electrode lead paste;

[0022] The negative electrode lead paste is prepared from the following components in parts by weight:

[0023] Barium sulfate 10-15 parts;

[0024] Fiber 0.8-1.2 parts;

[0025] 1-3 parts of lignin;

[0026] 3-5 parts of carbon black;

[0027] Lead powder 950-1050 parts;

[0028] 90-100 parts of deionized water;

[0029] 90-110 parts of dilute sulfuric acid.

[0030] Optionally, the negative electrode lead paste preparation method is as follows:

[0031] Pour the formulated amount of barium sulfate, fiber, lignin, and carbon black into a pot, add the formulated amount of lead powder, and dry stir for 5 to 10 minutes to obtain a mixture;

[0032] Add the formulated amount of deionized water to the prepared mixture and continue stirring for 3 to 5 minutes;

[0033] Add the formulated amount of dilute sulfuric acid, control the addition of sulfuric acid within 13 to 15 minutes, and continue stirring for 5 to 10 minutes.

[0034] Optionally, the preparation method of the negative electrode plate is as follows:

[0035] The negative electrode lead paste is applied on the negative electrode grid, 90-100g of the negative electrode lead paste is applied on each negative electrode grid, and the negative electrode lead paste covers the grid by 0.2-0.3mm to obtain a negative electrode plate. After the negative electrode plate is surface dried at 150-200°C, the negative electrode plate is cured and dried.

[0036] Optionally, the curing and drying adopts a temperature and high humidity curing process; the curing time is 24 to 48 hours, the curing temperature is 50°C, the relative humidity is 80 to 99%, the drying time is 20 to 24 hours, and the drying temperature is 60 to 80°C.

[0037] The above technical solution can improve the bonding strength between the negative electrode plate and the negative electrode lead paste.

[0038] In a second aspect, the present application provides a method for preparing the above-mentioned lightweight and long-life flooded battery, comprising the following steps:

[0039] S1, first prepare the positive electrode plate, the negative electrode plate and the separator;

[0040] S2, wrapping the positive electrode plate with a PE glass fiber layer, and casting and welding a plurality of positive electrode plates to obtain a positive electrode group, and casting and welding a plurality of negative electrode plates to obtain a negative electrode group;

[0041] S3, assembling the positive electrode group, the negative electrode group and the separator into a battery shell, wherein the positive electrode group, the negative electrode group and the battery shell are interference-fitted to obtain a battery.

[0042] In summary, the present invention reduces the weight by about 8% while keeping the battery capacity unchanged through structural design. By adopting a PE glass fiber separator, compared with a conventional separator, an additional PE layer is provided, thereby increasing the thickness of the electrode group. In conjunction with the structural design of the present application, the positive electrode group and the negative electrode group are interference-fitted in the battery shell, thereby reducing the shedding of active substances during the use of the battery and increasing the service life. DETAILED DESCRIPTION

[0043] The present application is further described in detail below with reference to the embodiments.

[0044] In the following examples of the present application, the main components involved, unless otherwise specified, were purchased from commercially available products. Specific embodiments

[0046] Preparation Example 1

[0047] This preparation example is used to prepare positive electrode lead paste, and the details are as follows.

[0048] Weigh the formula auxiliary materials (2.5-3 kg of sodium perborate, 1-2 kg of graphite, and 0.8-1 kg of glass fiber) and pour them into a pot, add 950-1050 kg of lead powder and dry stir for 5-10 minutes to obtain a mixture.

[0049] Add 90-110 kg of deionized water to the prepared mixture. After the deionized water is added, continue stirring for 3-5 minutes.

[0050] Add a density of 1.325 g / cm 3 90-100 kg of dilute sulfuric acid is added, and the sulfuric acid is added within 13-15 minutes. After the dilute sulfuric acid is added, continue stirring for 5-10 minutes.

[0051] Use a small amount of deionized water to fine-tune the lead paste to obtain an apparent density of 4.2 to 4.4 g / cm 3 The lead paste with high apparent density has low water content. In the subsequent curing and drying process, after the water in the lead paste evaporates, the lead paste in the plate has good bonding strength.

[0052] Preparation Example 2

[0053] This preparation example is used to prepare a positive electrode plate, and the details are as follows.

[0054] The lead paste prepared in Preparation Example 1 is applied on the positive electrode grid, and the weight of the electrode plate is controlled so that 100 to 110 g of lead paste is applied on each electrode plate. The coating weight of the lead paste is controlled so that the lead paste on the final electrode plate only covers 0.2 to 0.3 mm on the grid to obtain a positive electrode plate. After the electrode plate is surface dried in a surface drying kiln at 170 to 220° C., the electrode plate is cured and dried.

[0055] A medium temperature and high humidity curing process is adopted, wherein the curing time is 24 to 48 hours, the curing temperature is 50° C., the relative humidity is 80 to 99%, the drying time is 20 to 24 hours, and the drying temperature is 60 to 80° C.; a positive electrode plate is obtained.

[0056] Preparation Example 3

[0057] This preparation example is used to prepare negative electrode lead paste, and the details are as follows.

[0058] Weigh the formula auxiliary materials (barium sulfate 10-15 kg, fiber (polyester) 0.8-1.2 kg, lignin 1-3 kg, carbon black 3-5 kg) and pour them into a pot, add 950-1050 kg of lead powder and dry stir for 5-10 minutes to obtain a mixture.

[0059] Add 90-100 kg of deionized water to the prepared mixture. After the deionized water is added, continue stirring for 3-5 minutes.

[0060] Add 90-110 kg of dilute sulfuric acid with a density of 1.325 g / cm3 to the above mixture. Add the sulfuric acid within 13-15 minutes. After the addition of the dilute sulfuric acid is completed, continue stirring for 5-10 minutes.

[0061] Use a small amount of deionized water to fine-tune the lead paste to obtain an apparent density of 4.2 to 4.4 g / cm 3 The lead paste with high apparent density has low water content. In the subsequent curing and drying process, after the water in the lead paste evaporates, the lead paste in the plate has good bonding strength.

[0062] Preparation Example 4

[0063] This preparation example is used to prepare a negative electrode plate, and the details are as follows.

[0064] The negative electrode lead paste prepared in Preparation Example 3 is applied on the negative electrode grid, and the weight of the electrode plate is controlled so that 90-100 g of the lead paste is applied on each electrode plate, and the coating weight of the lead paste is controlled so that the lead paste on the final electrode plate covers only 0.2-0.3 mm on the grid to obtain a negative electrode plate. After surface drying in a surface drying kiln at 150-200° C., the electrode plate is cured and dried, and a medium-temperature and high-humidity curing process is adopted, wherein the curing time is 24-48 h, the curing temperature is 50° C., the relative humidity is 80-99%, the drying time is 20-24 h, and the drying temperature is 60-80° C.; the negative electrode plate is obtained.

[0065] Example

[0066] This embodiment is used to prepare a lightweight and long-life flooded battery, as follows.

[0067] Wrap the positive electrode plate prepared in Preparation Example 2 with a PE glass fiber layer, and cast-weld four positive electrode plates to obtain a positive electrode group, and cast-weld four negative electrode plates prepared in Preparation Example 4 to obtain a negative electrode group;

[0068] The positive electrode group, the negative electrode group and the PE glass fiber separator are assembled into the battery shell. The internal partition wall of the battery shell is designed with ribs to ensure that the electrode group and the battery cell are of interference design. The electrode plates in the electrode group are tightly pressed by the ribs to slow down the shedding of active materials during the use of the battery, thereby improving the cycle life of the battery. The positive electrode group, the negative electrode group and the battery shell are interference fit to obtain a battery.

[0069] The battery size prepared in this embodiment is:

[0070] Battery length: 207mm;

[0071] Battery width: 175mm;

[0072] Battery height: 190mm;

[0073] Weight: 17.69kg.

[0074] Comparative Example

[0075] This comparative example uses the Fengfan brand EFB-H6 start-stop battery, and the battery size is:

[0076] Battery length: 207mm;

[0077] Battery width: 175mm;

[0078] Battery height: 190mm;

[0079] The weight is 19.25kg.

[0080] The size of the battery prepared in the example of the present application is the same as the size of the battery in the comparative example, but the weight is reduced by 8% relative to the comparative example.

[0081] The batteries in the above embodiments and comparative examples were subjected to 100% DOD discharge cycle test (25°C).

[0082] The test method is as follows:

[0083] 1. Leave it for 1 hour

[0084] 2. Discharge at 68.4A until 1.75V / cell is reached;

[0085] 3. Charge for 10 hours at a constant voltage of 2.43V / cell and a current limit of 68.4A;

[0086] 4. Repeat steps 1-3 until the battery discharge capacity is lower than 0.5C and then terminate the test.

[0087] The test result of the battery in this embodiment is 682 times, and the test result of the battery in the comparative example is 438 times. The service life of the battery prepared by the technical solution of the present application is increased by more than 50% compared with that of the comparative example.

[0088] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A lightweight, long-life flooded battery, characterized in that: It includes a positive electrode group, a negative electrode group, a separator and a battery shell; the positive electrode group is composed of a plurality of positive electrode plates, and each positive electrode plate is wrapped by a PE glass fiber layer, the negative electrode group is composed of a plurality of negative electrode plates, and the positive electrode group, the negative electrode group and the battery shell are interference fit; the separator is a PE glass fiber separator.

2. The lightweight and long-life flooded battery according to claim 1, characterized in that: The positive electrode plate comprises a positive electrode grid and a positive electrode lead paste; The positive electrode lead paste is prepared from the following components in parts by weight: 2.5-3 parts of sodium perborate; 1-2 parts of graphite; Glass fiber 0.8-1 part; Lead powder 950-1050 parts; 90-110 parts of deionized water; 90-100 parts of dilute sulfuric acid.

3. The lightweight and long-life flooded battery according to claim 1, characterized in that: The preparation method of the positive electrode lead paste is as follows: Weigh the formulated amount of sodium perborate, graphite, and glass fiber into a pot, add the formulated amount of lead powder, and dry-mix for 5 to 10 minutes to obtain a mixture; Add the formulated amount of deionized water to the mixture and continue stirring for 3 to 5 minutes; Add the formulated amount of dilute sulfuric acid, and control the addition of sulfuric acid within 13 to 15 minutes. After the addition of dilute sulfuric acid is completed, continue stirring for 5 to 10 minutes.

4. The lightweight and long-life flooded battery according to claim 2, characterized in that: The preparation method of the positive electrode plate is as follows: The positive lead paste is applied on the positive grid, 100-110g of the positive lead paste is applied on each positive grid, and the positive lead paste covers the positive grid by 0.2-0.3mm to obtain a positive plate. After the positive plate is surface dried at 170-220°C, the positive plate is cured and dried.

5. The lightweight and long-life flooded battery according to claim 4, characterized in that: The curing and drying adopts a high-temperature and high-humidity curing process; the curing time is 24 to 48 hours, the curing temperature is 50° C., the relative humidity is 80 to 99%, the drying time is 20 to 24 hours, and the drying temperature is 60 to 80° C.

6. The lightweight and long-life flooded battery according to claim 1, characterized in that: The negative electrode plate comprises a negative electrode grid and a negative electrode lead paste; The negative electrode lead paste is prepared from the following components in parts by weight: Barium sulfate 10-15 parts; Fiber 0.8-1.2 parts; 1-3 parts of lignin; 3-5 parts of carbon black; Lead powder 950-1050 parts; 90-100 parts of deionized water; 90-110 parts of dilute sulfuric acid.

7. The lightweight and long-life flooded battery according to claim 6, characterized in that: The negative electrode lead paste preparation method is as follows: Pour the formulated amount of barium sulfate, fiber, lignin, and carbon black into a pot, add the formulated amount of lead powder, and dry stir for 5 to 10 minutes to obtain a mixture; Add the formulated amount of deionized water to the prepared mixture and continue stirring for 3 to 5 minutes; Add the formulated amount of dilute sulfuric acid, control the addition of sulfuric acid within 13 to 15 minutes, and continue stirring for 5 to 10 minutes.

8. The lightweight and long-life flooded battery according to claim 6, characterized in that: The preparation method of the negative electrode plate is as follows: The negative electrode lead paste is applied on the negative electrode grid, 90-100g of the negative electrode lead paste is applied on each negative electrode grid, and the negative electrode lead paste covers the grid by 0.2-0.3mm to obtain a negative electrode plate. After the negative electrode plate is surface dried at 150-200°C, the negative electrode plate is cured and dried.

9. The lightweight and long-life flooded battery according to claim 8, characterized in that: The curing and drying adopts a high-temperature and high-humidity curing process; the curing time is 24 to 48 hours, the curing temperature is 50° C., the relative humidity is 80 to 99%, the drying time is 20 to 24 hours, and the drying temperature is 60 to 80° C.

10. A method for preparing a lightweight and long-life flooded battery according to claim 1, characterized in that: The following steps are involved: S1, first prepare the positive electrode plate, the negative electrode plate and the separator; S2, wrapping the positive electrode plate with a PE glass fiber layer, and casting and welding a plurality of positive electrode plates to obtain a positive electrode group, and casting and welding a plurality of negative electrode plates to obtain a negative electrode group; S3, assembling the positive electrode group, the negative electrode group and the separator into a battery shell, wherein the positive electrode group, the negative electrode group and the battery shell are interference-fitted to obtain a battery.